Sistem Pakar Diagnosa Penyakit Mata Menggunakan Metode Certainty Factor Berbasis Android - Yogi Permana; I Gede Pasek Suta Wijaya; Fitri Bimantoro (Journal of Computer Science and Informatics Engineering (J-Cosine), 2017)
This entitled of research "Expert System Diagnosis Eye Diseases Using MethodCertainty Factor Based Android" is proposed due to the increased spread eye diseases thatis leads to blindness in Indonesia it is happened because of the limited facilities of eyehealth services in health centers and hospitals, as well as lack of eye doctor who canexamine the eye, making eye left untreated and can cause serious damage to the eye.Therefore, many people are already suffering from the early symptoms of blindnessletting untreated without properly treatment. The purpose of this study is to develop anexpert system that is capable of providing information about eye diseases along withsuggested solutions of the disease suffered by imitating the analysis of an eye doctor.The system is built using certainty factor method which is an algorithm that isimprove the uncertainty idea of an expert. This method is used to describe the level ofconfidence of experts on issues being addressed. This system is built by Ionic frameworkfor Android applications with PHP, HTML5 and AngularJS.The system is able to provide information about eye diseases through the processof diagnosis, that can be used for early treatment of eye diseases. The whole function ofthis expert system application already worked properly without any mistakes. Anddiagnostics accuracy rate of the system is 75% in the diagnosis process of 15 diseases and52 symptoms.